Pengaruh Pencahayaan terhadap Pembentukan Persepsi Visual Umat pada Masjid Al-Irsyad Bandung - Wangsa, Michael (Intra, 2015)
In Indonesia, 87.18% of the people are Muslim, praying in the mosque at Dawn, Midday, Asar, Maghrib and Isha. In West Java where the highest percentage of Muslims in Java alives, there is a mosque with the concept of space and the lighting condition aiming to give the sense of Gods people, namely Al-Irsyad Mosque, Bandung. This study was conducted to determine the effect of natural and artificial lighting to the formation of the visual perception of the presence of God and prayer 5 time difference for people in the mosque space. Researchers hope this research can maximize the design of religious buildings of Muslims in Indonesia. This research was conducted using qualitative method which is to analyze the questionnaire data. The analysis shows that overall on the five prayer times, the majority of respondents agreed the room lighting can give effect to the formation of visual perception or impression of the presence of God during prayer in the Al-Irsyad Mosque. Age, gender, eye health, prayer time, lighting sources (natural and / or artificial) that is received, and the people sitting position affects the clarity of seeing the cleric, the impression will be the lighting in the room, the impression will be the contrast of light, which as a whole will affect the formation of peopleâs visual perceptions of Gods presence in praying.